Urban-rural differences in plant and animal-based food intake among Indonesian adolescent girls: evidence from the 2014 Individual Food Consumption Survey - Febiani Riskika; Dodik Briawan; Ikeu Tanziha; Ummu Aiman; Linda Ayu Rizka Putri; Siti Ika Fitrasyah; Husnul Khatimah; Abdul Fandir (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada, 2026)
Background: Adolescence is a critical period of rapid growth requiring adequate and balanced nutrition. Early adolescence (10–12 years) represents an important window before menarche, during which optimal dietary intake supports growth and the accumulation of nutrient reserves. In Indonesia, differences in food access and socioeconomic conditions between rural and urban areas may contribute to disparities in adolescent dietary patterns.Objective: This study aimed to compare plant and animal-based food consumption between rural and urban adolescent girls aged 10–12 years in Indonesia using nationally representative data.Methods: This cross-sectional study analyzed secondary data from the 2014 Indonesian Individual Food Consumption Survey (IFCS), part of the Total Diet Study conducted by the Ministry of Health. A total of 4,577 adolescent girls aged 10–12 years were included. Dietary intake was assessed using a single 24-hour recall and classified into plant-based (cereals, tubers, legumes, vegetables, fruits) and animal-based (meat, fish, eggs, offal) food groups. Data were analyzed using descriptive statistics and the Mann–Whitney U test. Results: Urban girls consumed higher amounts of animal-based foods, particularly meat and eggs, whereas rural girls consumed more tubers and vegetables. However, several nutrient-dense food groups had a median intake of 0 g/day in both areas, indicating that more than half of respondents did not consume these foods on the recall day, while fruit intake was low across both settings. Conclusions: Urban–rural disparities in dietary patterns reflect unequal access to diverse and nutrient-rich foods. Strengthening school-based nutrition programs and adolescent-focused dietary strategies, particularly in rural areas, may help improve diet quality and reduce nutritional inequalities.